2019
DOI: 10.3390/nano9071003
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Effects of Pt-Shells on Nanostructures and Corresponding Oxygen Reduction Reaction Activity of Au-Cluster-Decorated NiOx@Pt Nanocatalysts

Abstract: Herein, ternary metallic nanocatalysts (NCs) consisting of Au clusters decorated with a Pt shell and a Ni oxide core underneath (called NPA) on carbon nanotube (CNT) support were synthesized by combining adsorption, precipitation, and chemical reduction methods. By a retrospective investigation of the physical structure and electrochemical results, we elucidated the effects of Pt/Ni ratios (0.4 and 1.0) and Au contents (2 and 9 wt.%) on the nanostructure and corresponding oxygen reduction reaction (ORR) activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…42 Accordingly, the CNP NCs exhibit suppressed pre-edge (R) and enhanced white line (Q) intensities in comparison to Ni-CNT, which apparently confirms the local distortion around Ni atoms and an increased extent of electron relocation from Ni 4s/4p orbitals to neighbouring atoms (Pd and/or Cu in the current study). 42 Besides, the position of the inflection point for CNP NCs is at higher energy levels compared to that of Ni foil (Figure S11) and similar to that of Ni-CNT confirming that Ni exists as NiOx. The coordination configurations of Ni-atoms in CNP NCs are further identified by the FT-EXAFS analysis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…42 Accordingly, the CNP NCs exhibit suppressed pre-edge (R) and enhanced white line (Q) intensities in comparison to Ni-CNT, which apparently confirms the local distortion around Ni atoms and an increased extent of electron relocation from Ni 4s/4p orbitals to neighbouring atoms (Pd and/or Cu in the current study). 42 Besides, the position of the inflection point for CNP NCs is at higher energy levels compared to that of Ni foil (Figure S11) and similar to that of Ni-CNT confirming that Ni exists as NiOx. The coordination configurations of Ni-atoms in CNP NCs are further identified by the FT-EXAFS analysis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Therefore, the major focus has been to reduce the amount of platinum used in the cathode. Development of Pt-based alloys, low-loadings of platinum, modifications of the support, and alternative metal catalysts have been considered [10][11][12][13][14]. For example, alloys of noble metals (Pt, Pd) and transition metals (Cu, Co) have been widely studied [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the aforementioned arguments and in line with recent developments, in the present study, we synthesized a ternary NC comprising hierarchical Ni@Pd NC with Pt-clusters decoration on the surface via a "self-aligned" heterogeneous nucleation-crystal growth mechanism on carbon black support (namely Ni@Pd-Pt). Our previous studies demonstrated that Pt-clusters decoration effectively shelters the catalyst surface from oxidation and creates intense active sites for HER facilitation [26][27][28][29][30][31]. In such a unique structure, Pt-clusters are decorated on the Ni@Pd surface and at the heteroatomic interfaces of Ni-to-Pd; where the ligand effect (due to difference in electronegativity of adjacent atoms) and lattice strain (due to lattice mismatch) plays a key role at the heterogenous interfaces and relocate electrons to the NC surface, hence, the formation of catalytic active sites takes place, which boosts the HER kinetics.…”
Section: Introductionmentioning
confidence: 99%